STRATEGI PENGEMBANGAN USAHA DISTILASI MINYAK DAUN CENGKEH DI DESA LUMBUTAROMBO KECAMATAN BANAWA SELATANKABUPATEN DONGGALA - Sulaeman Sulaeman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The goal of this research was to determine the proper strategy formulation for developing a business distillation of essential oils made from raw material of waste clove leaves located in Lumbotarombo Village, South Banawa District of Donggala Regency. The analitycal tool used to determine the feasibility of the strategy and business development was the SWOT (strenght, weaknesess, opportunities and threats) analysis.The stages in the SWOT analysis were internal and external factor identification of the company, IFAS and EFAS determination, SWOT diagram construction, and SWOT diagram matric formation.  It is found that the formulation for appropriate development strategy was S-O (strenghts–opportunities) strategy in whichthe strengths were utilized in order to take advantages of the opportunities through maximizing the use of technology to increase production to meet consumer demand, rising price of the product simultaneously with an increase in the quality of products generated in a way of choosing raw materials more selectively and balancing the price of the product with that of raw materials so people could been courage in collecting clove leaves and production can be increased to met consumer demand. Key Words : Internal and external factors, strategy development, and SWOT analysis.